Strategi Pemasaran dalam Penerapan Digital Marketing pada Kewirausahaan UMKM Kuliner: Studi Kasus pada “Bakso dan Mie Ayam Mami Inung” di Rajabasa, Bandar Lampung - Daud, Syahril; Maxentia, Cindy; Paolo, Clarissa Chandra; Tanuhardja, Ferdinand (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Technological advances have brought significant changes in the business world, especially through digital marketing which provides great opportunities for UMKM to increase revenue and competitiveness. This research aims to analyze the digital marketing strategies implemented by UMKM “Bakso and Mie Ayam Mami Inung” in Bandar Lampung, with a focus on optimizing social media and e-commerce platforms. This research uses a qualitative approach with descriptive methods, involving in-depth interviews, participatory observation, and document analysis. The results show that digital marketing strategies such as the utilization of social media, delivery platforms, and collaboration with influencers can increase product visibility and accessibility. However, challenges such as lack of digital skills and fierce competition are still major obstacles. SWOT analysis identified a great opportunity in utilizing technology to reach a wider market. Implementation of strategies such as creative content creation, discount promotions, and marketing data analysis are recommended to improve business sustainability. This research provides insights for other UMKM in developing effective digital marketing strategies to improve competitiveness in the digital era.